Redke pridobljene motnje hemostaze kot vzrok podaljšanih krvavitev s prikazom dveh primerov - Novak, Polona (Zdravniški vestnik, 2011)
Background: Patientćs anamnesis is of primary importance in determining hemostatic disorders. Based on anamnestic data, a clinician may decide for further laboratory tests. We must consider an acquired bleeding disorder in a patient with unusual, unexpected and prolonged bleeding episodes. In this article we will describe two rare acquired hemostatic disordes. Two case reports: Our first patient had prolonged bleeding after a pacemaker implantation. We diagnosed him with acquired von Willebrand syndrome. Further on, the patient required a planned surgical procedure. In our second case we describe a patient with unusual and excessive skin bruising and prolonged bleeding after teeth extractions. He was diagnosed with acquired hemophilia. Conclusion: In the assessment of a patient with a potential acquired bleeding disorder we must first rule out the most common causes, such as iatrogenic ones. But, because of high morbidity and mortality rates, we must also be aware of some rare acquired bleeding disorders. In case of uncertainty, we should consult with a hematologist.
Keywords: hemofilija; hemostaza; krvavitev; motnje